Design of High-Voltage Isolation Multi-Output Power Supply for IGCT Gate Drive - CHEN Xiulin; WANG Sanhu; ZOU Yangju (Kongzhi Yu Xinxi Jishu)
This paper addresses the issues of floating high voltage at light loads and insufficient cross-regulation in open-loop high-isolation multi-output power supplies. It initially introduces methods of separate winding arrangements and core projection coincidence to reduce distributed capacitance and leakage inductance in transformers. Subsequent analysis reveals the impact of distributed capacitors on converter gain based on the fundamental harmonic wave analysis method. Additionally, a series compensation method is utilized to mitigate this impact of leakage inductance on convertor gain. This combination leads to the development of a CLLC resonant converter with an asymmetric structure. Finally, the paper presents the development of a 4-output prototype with a total output power of 420 W. Testing results indicate that both the primary and secondary sides of transformer meet an AC18 kV isolation requirement. The voltage accuracy of power output across the full load range is controllable within ± 10%. In fault mode, the faulty branch actively shuts off the output, while normal functioning is maintained in the other branches, verifying the correctness of the proposed design scheme.